Perancangan Sistem Pendukung Keputusan Penentuan Prioritas Proyek Pengembangan Aplikasi pada CV BOSpintar Jaya - Yusman, Beny; Fadel, Moh.; M. Syafiih; Muafi; Bambang (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2026)
CV BOSpintar Jaya, a company engaged in application development services, faces challenges in determining project priorities when multiple development requests are received within a limited timeframe. Priority determination that relies on subjective judgment may lead to project delays, inefficient resource allocation, and decreased client satisfaction. This study aims to design a Decision Support System (DSS) to assist management in objectively and systematically determining the priority of application development projects. The research methodology includes requirements analysis, identification of project alternatives and decision criteria, criteria weighting, decision model design, as well as system interface and database design. The criteria used include project value, urgency level, development complexity, estimated duration, risk of requirement changes, and availability of developer resources. The calculation process produces preference values and project rankings as recommendations for project prioritization. The results show that the designed DSS is able to provide consistent, transparent, and traceable priority recommendations, thereby supporting faster and more accurate decision-making while reducing dependence on subjective assessments. The proposed DSS is expected to improve project planning efficiency, optimize resource allocation, and enhance the quality of application development services at CV BOSpintar Jaya.